The Association Between Emotion Recognition, Affective Empathy, and Structural Connectivity in Schizophrenia Patients - Koevoets, Martijn G. J. C.; Prikken, Merel; Hagenaar, Doesjka A.; Kahn, René S.; van Haren, Neeltje E. M. (Frontiers in Psychiatry, 2022)
Emotion processing deficits often occur in patients with schizophrenia. We investigate whether patients and controls differ in the association between facial emotion recognition and experience of affective empathy and whether performance on these emotion processing domains differently relates to white matter connectivity. A tot al of 47 patients with schizophrenia and 47 controls performed an emotion recognition and affective empathy task. T1-weighted and diffusion-tensor images (DTI) of the brain were acquired. Using Tracula5.3, ten fibers were reconstructed and fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (AD), and radial diffusivity (RD) were extracted. Groups were compared on task performance, white matter measures and their interactions using ANCOVAs. Correction for multiple comparisons was applied. Patients scored lower on emotion recognition (p=0.037) and reported higher levels of affective empathy (p<0.001) than controls. Patients with poor emotion recognition (PT-low) experienced stronger affective empathy than patients with similar emotion recognition performance as controls (PT-normal; p=0.011), who in turn reported stronger affective empathy than controls (p=0.043). We found a significant interaction between emotion recognition, affective empathy and anterior thalamic radiation AD (p=0.017, d=0.43). Post-hoc analyses revealed that the correlation between AD and empathy differed significantly between all groups (empathy/AD in PT-low < empathy/AD in PT-normal < empathy/AD in controls). In patients with poor emotion recognition, the negative association between anterior thalamic radiation AD and affective empathy was stronger than in patients with normal emotion recognition capacity. Possibly, demyelination in fronto-thalamic structural connections, as part of a larger frontotemporal network, underlies the association between poor emotion recognition and higher levels of affective empathy in schizophrenia patients.